Photoacoustic monitoring of angiogenesis predicts response to therapy in healing wounds. Issue 2 (12th January 2022) - Mantri, Yash; Tsujimoto, Jason; Donovan, Brian; Fernandes, Christopher C.; Garimella, Pranav S.; Penny, William F.; Anderson, Caesar A.; Jokerst, Jesse V.
Abstract: Chronic wounds are a major health problem that cause the medical infrastructure billions of dollars every year. Chronic wounds are often difficult to heal and cause significant discomfort. Although wound specialists have numerous therapeutic modalities at their disposal, tools that could three dimensional‐map wound bed physiology and guide therapy do not exist. Visual cues are the current standard but are limited to surface assessment; clinicians rely on experience to predict response to therapy. Photoacoustic (PA) ultrasound (US) is a non‐invasive, hybrid imaging modality that can solve these major limitations. PA relies on the contrast generated by haemoglobin in blood which allows it to map local angiogenesis, tissue perfusion and oxygen saturation—all critical parameters for wound healing. This work evaluates the use of PA‐US to monitor angiogenesis and stratify patients responding versus not‐responding to therapy. We imaged 19 patients with 22 wounds once a week for at least 3 weeks. Our findings suggest that PA imaging directly visualises angiogenesis. Patients responding to therapy showed clear signs of angiogenesis and an increased rate of PA increase ( p  = 0.002). These responders had a significant and negative correlation between PA intensity and wound size. Hypertension was correlated to impaired angiogenesis in non‐responsive patients. The rate of PA increase and hence the rate of angiogenesis was able to predict healing times within 30 days from the start of monitoring (power = 88%, alpha = 0.05). This early response detection system could help inform management and treatment strategies while improving outcomes and reducing costs.